Traveling on land - Chancellor, Deborah (Princeton, N.J. : Two-Can, 2001)
Investigates different modes of transportation used around the world, including elephants, motorcycles, trucks, and subway trains, and concludes with a look at the future of ground transportation.
Includes index.
Ages 8-11.
Keywords: Transportation -- Juvenile literature; Transportation